SYLLABUS AND CURRICULUM DESIGN FOR SECOND LANGUAGE TEACHING DTPI FOREIGN LANGUAGE AND LITERATURE - Yoqubova Mohichehra; Yoʻldosheva Marjona; Toʻraxonova Marjona (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation This article explores the concepts of syllabus and curriculum design in second language (L2) teaching. It highlights the importance of structured planning in achieving effective language learning outcomes. The study examines different types of syllabi, principles of curriculum design, and their role in developing learners’ communicative competence. It also discusses how modern approaches and technology contribute to improving language teaching. The research shows that well-designed curriculum and syllabus play a crucial role in enhancing language skills, learner motivation, and overall educational success.